Towards strategies to capture and retain mobile ticketing customers - Campos Ferreira, Marta; Ferreira, Catarina; Galvão Dias, Teresa (EAI Endorsed Transactions on Smart Cities, 2021)
INTRODUCTION: When compared to traditional ticketing systems, mobile ticketing has several advantages, allowing ubiquitous and remote access to payments, avoiding queues and replacing notes and coins. It also allows service providers to reduce their costs and achieve operational and productivity gains. However, while some cities have implemented mobile ticketing solutions on their public transport network, the adoption of such services appears to have limited success. The causes that lead to such a low rate of use of the service are still unknown.OBJECTIVES: This paper presents an in-depth study of the reasons that lead mobile ticketing customers to adopt or abandon this type of service and establishes a series of strategies to attract and retain customers.METHODS: It uses the city of Porto, Portugal, as an illustrative example, where a mobile ticketing solution, called Anda, was launched. Customer complaints related to 6 months of using Anda were analysed and usability tests were carried out with real customers in the context of use.RESULTS: This analysis allowed to identify a series of factors that lead people to adopt or abandon this type of services. Then, a series of strategies were defined and identified that allow to capture and retain mobile ticketing customers during the various stages of the mobile ticketing lifecycle: user onboarding, user engagement, user retention and user reinstall. For each of the stages of this life cycle, the main concerns to be considered were also listed, a series of tactics were defined to reverse the abandonment trend and a series of KPIs were specified to measure the efficiency of the strategies.CONCLUSION: This paper fills an important research gap in the literature, being very useful in shaping future strategies for successful mobile ticketing solutions.
Keywords: mobile ticketing; urban passenger transport; customer loyalty; customer churn